Dissemination and Assistance on Coretax Activation for Taxpayers at UIN Sultanah Nahrasiyah Lhokseumawe - Isra maulina; Juliana Putri; Putri Nabila (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2026)
Digital transformation in tax administration through the implementation of the Coretax Administration System (Coretax) has become a strategic initiative by the government to improve service efficiency, transparency, accountability, and taxpayer compliance. This community service activity aims to enhance taxpayers’ understanding, skills, and independence through the socialization and assistance of Coretax activation in UIN Sultanah Nahrasiyah Lhokseumawe. The method used in this activity was Participatory Action Research (PAR), which consisted of preparation, socialization, training, hands-on practice, mentoring, and evaluation stages. The participants were individual taxpayers ASN UIN Sultanah Nahrasiyah Lhokseumawe. The results of the activity indicated an improvement in participants’ understanding of the functions and benefits of Coretax, technical abilities in account activation, as well as digital skills in using electronic tax administration systems. The level of participant involvement was also relatively high, reflecting taxpayers’ enthusiasm for practice-based mentoring programs. These findings reinforce the Technology Acceptance Model (TAM), which emphasizes that perceived ease of use and perceived usefulness influence technology acceptance. In addition, experiential learning and andragogical approaches proved effective in improving participants’ understanding through direct experience. Therefore, the socialization and mentoring of Coretax activation can serve as a strategic model in supporting the success of digital transformation in taxation and the sustainable improvement of taxpayer compliance.